FAKTOR EKONOMI DAN IMPLEMENTASI TUGAS KESEHATAN KELUARGA PADA PENDERITA HIPERTENSI - Hia, Murni Hartatai; Patras, Syalomita F.S; Adu, Tata Suela; Diannita, Catharina Guinda; M.J.P Sihaloho (JURNAL KEPERAWATAN, 2024)
Background: Hypertension is often referred to as the "silent killer" because people with hypertension often do not feel signs and symptoms. In 2022, the incidence of hypertension at the Jalan Kutai Health Center, Bencongan Indah Village, was 2,854 people. The process of monitoring, maintaining, and preventing complications of hypertension requires the role and support of the family to carry out family health tasks. Objective: This study aimed to identify the correlation between economic factors and family health tasks for people with hypertension in Bencongan Indah Village. Methods: This study used a quantitative descriptive research method with a cross-sectional approach and bivariate data analysis. Samples were selected using the purposive sampling method, with a total of 114 participants calculated using the Lemeshow formula. The research instrument was a modified questionnaire with 25 questions that had been tested for validity and reliability. Results: The study found that the ability of families to recognize health problems was still low (58.8%), the ability of families to decide on appropriate health measures was high (71.1%), the ability of families to care for sick family members was high (58.8%), the ability of families to modify the environment was still low (57%), and the ability of families to utilize health facilities was high (52.6%). There was no relationship between economic factors, as described by monthly family income, and family health tasks (p-value > 0.05). Conclusion: It is expected that families will be able to recognize the health problems of sick family members and make changes or modifications to their environment to support the care of family members who face health problems